PRAGMATIC POTENTIAL AND COMPONENTS OF PHRASEOLOGICAL UNITS IN ENGLISH - ГЛУХОВСЬКА, Марина (Current Issues of Foreign Philology, 2022)
Some study of phraseology as a subsystem of language involves detailed study of general and special issues, including some problems of meaning of phraseological unit, its reflection in lexicography, as well as the functioning of phraseological unit in modern English. In the first stages of development of phraseological science, such issues as integrity of meaning, constancy of reinterpreted phrases, their ability to play the role of certain members of the sentence and function as a separate word were studied. On the basis of English, studding of phraseological meaning took place in different aspects wite using of different methods and techniques in many works of different scholars. But despite of a lot of researches which were dedicated to phraseological units, these problems have not yet been definitively resolved. This is due to the complexity of phraseological semantics, as well as the lack of a single view in addressing pragmatic potential of phraseological meaning, semantic processes that formed the basis of its formation and so on. Speaking about the theoretical foundations of phraseological meaning, it is necessary, first of all, establish the concept of phraseological units, because the definition of characteristic or differential features of phraseology depends on the study of phraseology as a whole and its individual aspects. The study of the pragmatic potential and components of the phraseological units of the English language should show some specific features of phraseological meaning of language. No less important is their study to identify features of creating linguistic picture of the world, establishing the mechanism of action of human factors in language. It is believed that phraseological unit will contribute to the understanding of both cognitive and pragmatic aspects of language. Modern linguistics is inconceivable without comparing the studied objects. Mutual correlation, comparison and juxtaposition of units, forms, categories and other linguistic phenomena acts as a prerequisite for characterizing each of them, establishing significant formal and semantic connections between them and constituting their connecting microsystems, subsystems and systems. The above also applies to the study of phraseological units. It can even be argued that in the field of phraseological research the need for comparison is higher than at other levels of analysis.